Revitalization Of Panji Mask Through Performing Arts In The Perspective Of Cultural Communication - Ferdian Candra Maulana; Zulaikha Zulaikha; Didik Sugeng Widiarto (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
The influence of modern culture cannot be denied as being related to the declining interest of the younger generation in traditional arts such as Topeng Panji. Therefore, revitalization efforts through adaptive cultural communication strategies are needed. This study aims to analyze cultural communication strategies and their impact on the formation of cultural identity among the younger generation. The research was conducted using a qualitative approach. Data were collected from four informants, including the head of the cultural office, a curator, a dancer, and audience members, using interview and documentation techniques. The findings reveal that revitalization strategies through performance innovation, digitalization, and education are effective in conveying cultural values and building cultural identity across the five dimensions of Cultural Identity Theory: personal, enacted, relational, communal, and material identity. Meanwhile, from a semiotic perspective, Topeng Panji contains meaning at every level. At the denotative level, the meanings are manifested through visual performances; at the connotative level, they are reflected in moral and philosophical values; and at the mythical level, they appear in the naturalization of cultural ideology conveyed through the performance.